Implementasi Program Sistem Manajemen Aplikasi Rakyat Terpadu Badan Pendapatan Daerah (Smart Bapenda) Pada Badan Pendapatan Daerah Kabupaten Sukabumi Tahun 2024-2025 - Maulana Mansyur; M. Rijal Amirulloh; Yana Fajar FY. Basori (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2026)
Local tax services still face several challenges, including inefficient procedures, limited service access, and low public awareness and compliance in paying taxes. These conditions encouraged the Regional Revenue Agency of Sukabumi Regency to introduce an innovation through the Integrated Public Application Management System Program (SMART BAPENDA) as part of the Tax and Levy Payment Awareness Movement through Integrated Public Services (GEBYAR SIPENYU). This study aims to analyze the implementation of the SMART BAPENDA Program at the Regional Revenue Agency of Sukabumi Regency in 2024–2025 using the policy implementation theory of Van Meter and Van Horn (1975). The research uses a qualitative descriptive method. Data were collected through observation, interviews, and documentation, with informants selected using snowball sampling involving leaders, policy implementers, and community members. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that the implementation of SMART BAPENDA is fairly effective, particularly in terms of clear policy standards and objectives, relatively good inter-organizational communication, and the commitment and discipline of policy implementers. The program improves access to tax services, enhances time and cost efficiency, and increases public awareness of local tax obligations. However, the implementation has not been fully optimal due to limited resources, especially budget constraints, technological system capacity, and gaps in public digital literacy. In conclusion, although SMART BAPENDA is fairly effective, strengthening resources and improving community digital literacy are necessary for more optimal implementation.